The Influence of Payroll and Internal Control on the Effectiveness of Accounting Information System - Rara Prastiwi; Harsi Romli; Vhika Meiriasari (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine how much influence the payroll information system and wage information system have on the effectiveness of internal control by conducting tests using SPSS version 23. This research was conducted on respondents who were employees at PT Pratama Palm Abadi with a total sample size of 70 respondents. This research uses quantitative methods and the analysis used is multiple linear regression analysis. The results of the first regression analysis prove that the payroll information system (X1) has a significant effect on the effectiveness of internal control, which means that H1 is proposed to be accepted. With the increase in the payroll information system, it has a positive impact on increasing the effectiveness of internal control. This means that the payroll information system has a positive effect on the effectiveness of internal control. The second regression result proves that the wage information system (X2) has a positive effect on the effectiveness of internal control, which means that H2 is accepted. Together the variables of the wage information system (X1) and the wage information system (X2) have a positive effect on the effectiveness of internal control